2015
DOI: 10.1590/0104-6632.20150322s00003371
|View full text |Cite
|
Sign up to set email alerts
|

Self-Similarity of Vertical Bubbly Jets

Abstract: -An integral model for vertical bubbly jets with nearly monodisperse bubble sizes is presented. The model is based on the Gaussian type self-similarity of mean liquid velocity, bubble velocity and void fraction, as well as on functional relationships for initial liquid jet velocity and radius, bubble diameter and relative velocity. Adjusting the model to experimental data available in the literature for a wide range of densimetric Froude numbers provide constant values for the entrainment coefficient, momentum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
(64 reference statements)
1
0
0
Order By: Relevance
“…At subsonic velocities (M < 1) the jetting regime is unstable [14] and for y > H j the continuous jet is transformed into a bubble stream, as is observed in Figure 1. Jet heights were determined from the phase distributions and are depicted in Figure 2 Figure 3 shows that the argon volume fraction exhibits a Gaussian distribution inside the jets as reported experimentally in [24] and numerically in [25] [26]. Besides, in Figure 3 it is observed that the volume fraction and the width of the jets are increased as the injection velocity is increased.…”
Section: Methodssupporting
confidence: 55%
“…At subsonic velocities (M < 1) the jetting regime is unstable [14] and for y > H j the continuous jet is transformed into a bubble stream, as is observed in Figure 1. Jet heights were determined from the phase distributions and are depicted in Figure 2 Figure 3 shows that the argon volume fraction exhibits a Gaussian distribution inside the jets as reported experimentally in [24] and numerically in [25] [26]. Besides, in Figure 3 it is observed that the volume fraction and the width of the jets are increased as the injection velocity is increased.…”
Section: Methodssupporting
confidence: 55%